A review of insecticidal effect of essential oils on stored grain pests - Leite , Bruna Martinelli; Cunha, Felipe Alexsander; Bertozzi , Bruno Gerfi; Rocha , Liliana de Oliveira; Queiroz , Lorena Carnielli (Food Science and Technology, 2023)
Grain production grows more every year, and stored grain pests have been a challenge for agriculture. The use of pesticides is the main solution to face this challenge; however, improper and extensive management leads to another difficulty: the resistance acquired by some pests, causing their ineffectiveness. Thus, essential oils and other natural products emerge as an alternative to overcome this situation. In this study, several essential oils with insecticidal/repellent properties were reviewed to evaluate the capacity to become an important method for protecting stored grains against the most recurrent pests. This is a literature review that analyzed articles in scientific database platforms, using different combinations of the keywords “Essential oils”, “Insecticides”, “Stored grains”, “Repellents” and “Insects”. Among the essential oils studied, the most outstanding were the essential oils of: Artemisia argyi and Mentha haplocalyx against Lasioderma serricorne; Artemisia rupestris and Ligusticum pteridophyllum against Liposcelis bostrychophila; and Artemisia anethoides, Elshotzia ciliata, and Amomum maximum against Tribolium castaneum. Along with some essential oils, their main components and insecticidal/repellent capacity when isolated were also evaluated. The results were promising, although mechanisms of action have not yet been elucidated. Investing in research for alternative pest control can contribute to sustainable agriculture.